New Possibilities of Knowledge Transfer by Playing Manager Games. (12th February 2015) - Ottova, Michaela; Kudrna, Jiri; Poor, Peter; Edl, Milan
Abstract: The aim of this article is to describe the current view on concept of education for sustainable development. The role of universities nowadays became more complex and one of the essentials is to create and enhance partnership between universities and practice. Specifically, it is the transfer of theoretical research knowledge base to practice. One of the ways how to realize this transfer by simple and comfort way is using manager games.